2015
DOI: 10.2134/agronj14.0086
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Sheep Grazing into Cereal‐Based Crop Rotations: Spring Wheat Yields and Weed Communities

Abstract: Crop diversification and integration of livestock into cropping systems may improve the economic and environmental sustainability of agricultural systems. However, few studies have examined the integration of these practices in the semiarid areas of the Northern Great Plains (NGP). A 3-yr experiment was conducted near Bozeman, MT, to compare the effects of crop rotation diversity and weed management practices imposed during fallow periods [sheep (Ovis aries) grazing, reduced tillage, and conventional tillage] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Research is being conducted on a variety of cropping systems to develop more effective integrated weed management methods that are ultimately sustainable and reduce reliance on herbicides (Lechenet et al ., 2017). Investigations into the effects of including livestock grazing in crop-based systems have demonstrated that, compared with conventional cropping systems, ICLSs can result in lower of weed infestation as well as lower costs and risks associated with herbicide usage (Tracy and Davis, 2009; Miller et al ., 2015; Lehnhoff et al ., 2017). However, these investigations revealed that, in some years, livestock led to an increase in weed infestation in arable lands (Miller et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research is being conducted on a variety of cropping systems to develop more effective integrated weed management methods that are ultimately sustainable and reduce reliance on herbicides (Lechenet et al ., 2017). Investigations into the effects of including livestock grazing in crop-based systems have demonstrated that, compared with conventional cropping systems, ICLSs can result in lower of weed infestation as well as lower costs and risks associated with herbicide usage (Tracy and Davis, 2009; Miller et al ., 2015; Lehnhoff et al ., 2017). However, these investigations revealed that, in some years, livestock led to an increase in weed infestation in arable lands (Miller et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The re‐integration of crop and livestock production offers the potential to improve the sustainability of farming systems by managing weed and insect pest populations, improving soil quality, increasing yield, augmenting pollinator populations and improving land use efficiency (Hilimire, ). While effects of mixed crop and livestock systems on farm productivity and profitability have been documented (Tracy & Davis, ; Miller et al ., ), the role that animal grazing could have as a filtering factor conditioning the assembly of weed communities is largely unknown. The goal of this study was to evaluate the impact of cropping system (a perennial [lucerne] vs. an annual (continuous spring wheat, CSW) and contrasting weed management practices in CSW (mechanical, chemical and sheep grazed) on weed abundance, diversity and community composition.…”
Section: Introductionmentioning
confidence: 99%
“…(2019). Fewer weed problems occurred in crop rotations that included forages (Entz et al., 1995, 2002; Miller, Menalled, Sainju, Lenssen, & Hatfield, 2015). Field crop yield and overall system economics were improved by incorporating animal grazing into cropping schemes (Kumar et al., 2019).…”
Section: Animal Integration Into Organic Field Crop Systemsmentioning
confidence: 99%